2016
DOI: 10.4103/0971-3026.195795
|View full text |Cite
|
Sign up to set email alerts
|

Restricted diffusion in the corpus callosum: A neuroradiological marker in hypoxic–ischemic encephalopathy

Abstract: Background:Restricted diffusion within the splenium of the corpus callosum has been described by other authors in various conditions, however, restricted diffusion in the entire corpus callosum or isolated involvement of the splenium, genu, or body has been infrequently reported on magnetic resonance imaging (MRI) in neonatal hypoxic–ischemic encephalopathy. We report a series of cases showing different patterns of involvement.Methods and Materials:Perinatal imaging with MRI including diffusion-weighted imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Moreover, diffusion abnormality was associated with lower APGAR score at 10 min, higher mortality, higher proportion requiring intubation during the first few minutes of life, and greater seizure burden. Kelkar and colleagues reported on 16 (40%) neonates with different patterns of corpus callosum involvement, of which 15 had splenium changes [ 13 ]. Kumar et al found 11 (40%) of their patients had restricted diffusion within the corpus callosum, all of whom had splenium changes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, diffusion abnormality was associated with lower APGAR score at 10 min, higher mortality, higher proportion requiring intubation during the first few minutes of life, and greater seizure burden. Kelkar and colleagues reported on 16 (40%) neonates with different patterns of corpus callosum involvement, of which 15 had splenium changes [ 13 ]. Kumar et al found 11 (40%) of their patients had restricted diffusion within the corpus callosum, all of whom had splenium changes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al found 11 (40%) of their patients had restricted diffusion within the corpus callosum, all of whom had splenium changes [ 15 ]. Both of these studies found that corpus callosum injury was associated with more extensive brain injury [ 13 , 15 ]. We similarly found 69.2% of our neonates with restricted diffusion in the splenium had at least 2 or more other brain regions affected (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal hypoxic-ischemic encephalopathy is a serious complication in clinical medicine. Although its pathogenesis has not been fully explained, relevant research results indicate that it is largely related to placental abnormalities, heart failure and other factors (8)(9)(10). When neonatal hypoxic-ischemic encephalopathy occurs, the patient experiences gas exchange disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of HIE are associated with risk factors arising before the onset of labor including maternal factors, placental conditions, and fetal problems. It is not only a serious threat to newborns, but also extends into childhood ( Kale et al, 2016 ). Since the 1990s, multicenter randomized controlled studies of therapeutic hypothermia for neonatal HIE were confirmed ( Chalak et al, 2014 ), therapeutic hypothermia has been proven to be safe, reliable, and have a curative effect, and can significantly reduce the neurological sequelae and degree of disability caused by HIE ( Jacobs et al, 2013 ; Pauliah et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%